PENGARUH MODEL MAKE A MATCH BERBANTUAN MEDIA PAPAN PERKALIAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Aprilia Khoirun Nisa; Denna Aji Prameisthi; Hanik Noor Solikhah; Wahyu Amaruddin; Fitriyah Amaliyah (Jurnal PGSD Musi, 2023)
This study aims to determine the effect of the Make a Match model assisted by multiplication board learning media on the mathematical problem solving abilities of class II students at SD Negeri 6 Cendono, Kudus. This study used a pre-experimental design with the One Group Pre-test Post-test Design model. Determination of the subjects of this study were selected using non-probability sampling with saturated sampling. The sample used was 10 students, while the instrument in this study used a data collection method in the form of description questions which had been validated to contain indicators for assessing the mathematical problem solving abilities of class II students. Data analysis was performed using a parametric statistical test, namely the Paired Sample T-test. The results showed that the significance value ? 0.000 <0.05. This means that Ho is rejected and Ha is accepted. so it can be concluded that the use of the Make a Match learning model with the help of multiplication board media has a significant effect on the mathematical problem solving abilities of Class II students at SD 6 Cendono.